The Influence of Training on Teacher Performance: The Mediating Role of Emotional Intelligence - Adelia Dwi Nurisaputri; Ahmad Ari Sasongko; Amikasia Thalia Nalora; Yuni Siswanti (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2025)
This study aims to examine the influence of training on teacher performance with emotional intelligence as a mediating variable at Pondok Pesantren Taruna Al-Qur’an Yogyakarta. The research employed a quantitative approach using a questionnaire distributed to 43 teachers as respondents. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The findings show that training has a positive and significant effect on teacher performance, both directly and indirectly through emotional intelligence. Emotional intelligence is proven to play a mediating role in strengthening the relationship between training and teacher performance. The study concludes that effective training not only enhances professional competence but also fosters emotional and interpersonal skills, which are essential for improving the overall quality of education in Islamic boarding schools.